Short Communication: Potential threats to seagrass in the waters of Tanah Bumbu District, South Kalimantan, Indonesia - DAFIUDDIN SALIM; ROHANI AMBO-RAPPE; SUPRIADI MASHORENG; NADIARTI NURDIN KADIR (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Salim D, Ambo-Rappe R, Mashoreng S, Kadir NN. 2024. Short Communication: Potential threats to seagrass in the waters of Tanah Bumbu District, South Kalimantan, Indonesia. Biodiversitas 25: 1882-1889. Seagrass meadows are one of the most productive coastal communities, but they are easily degraded or lost due to declines in water quality. This study was conducted to analyze the potential threats to seagrass in the waters of Tanah Bumbu District, South Kalimantan, caused by increased turbidity from sedimentation and resuspension, the occurrence of invasive species, macroalgal and epiphytic cover on seagrasses. Field surveys on three coral cays (i.e. (Anugrah, Penyulingan and Katoang) and a literature study were conducted to collect data on sedimentation rate, total suspended solids (TSS), climate and precipitation, invasive species, and percentages of seagrass, macroalgae and epiphyte cover. Results showed a sedimentation rate of 46.66 mg/cm2/day and TSS range of 0.83-774.8 mg/l. These parameters were likely influenced by changes in land cover, sediment loads from surrounding rivers, climate, and port activity, especially at coal and palm oil terminals. An invasive species, i.e. zebra mussel (Dreissena spp.), was found on seagrass, and this is the first report of such an occurrence on seagrasses. The overall average percentage of seagrass, epiphyte and macroalgae cover on Anugrah, Penyulingan and Katoang coral cays were 33±26.78%; 37.68±29.31%; and 2.43±1.77%, respectively. The results of this study imply that seagrass ecosystems in Tanah Bumbu are threatened by increased turbidity, minimum light penetration, fluctuations in salinity, and the occurrences of competitors (invasive species and macroalgae).